2015
DOI: 10.16970/ted.62843
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Turkish wild Emmers (Triticum dicoccoides Koern.) and wheat varieties cultivars for resistance to the root lesion nematodes (Pratylenchus thornei and Pratylenchus neglectus)

Abstract: Evaluation of Turkish wild Emmers (Triticum dicoccoidesKoern SummaryRoot-lesion nematodes (RLN; Pratylenchus thornei and Pratylenchus neglectus) are serious plant parasitic nematodes that attack wheat roots and cause significant losses in grain quality and quantity worldwide. They are widely distributed in Turkish wheat growing areas and can be only controlled by growing resistant cultivars and nonhost crops. So far, there is no commercial wheat cultivar identified as completely resistant to the RLN is availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…neglectus (Rensch, 1924) Filipjev &Schuurmans Stekhoven, 1941], were the most widely distributed species. Toktay et al (2015) reported that 56% of wheat fields were infested with H. filipjevi in Elazig, Erzincan, Erzurum, Igdir, Kars, Malatya and Sivas Provinces in the East Anatolia Region of Turkey. Imren et al (2016) reported that 83% of wheat fields were infested with H. filipjevi, in Bolu Province, Turkey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…neglectus (Rensch, 1924) Filipjev &Schuurmans Stekhoven, 1941], were the most widely distributed species. Toktay et al (2015) reported that 56% of wheat fields were infested with H. filipjevi in Elazig, Erzincan, Erzurum, Igdir, Kars, Malatya and Sivas Provinces in the East Anatolia Region of Turkey. Imren et al (2016) reported that 83% of wheat fields were infested with H. filipjevi, in Bolu Province, Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Imren et al (2015) did not found any genetic differentiation between H. filipjevi populations in the Mediterranean Region of Turkey. However, Subbotin et al (2010) reported intraspecific polymorphism between H. filipjevi populations and Toktay et al (2015) also found intraspecific variation between populations in H. filipjevi from the Eastern Anatolian Region of Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is not feasible to use nematicide for control root lesion and cyst nematodes in wheat. So, studies on screening of resistant wheat genotypes and management strategy have been carried out in Turkey in recent years (Dababat et al, 2015;İmren et al, 2015;Toktay et al, 2015). Meloidogyne arenaria (Neal, 1889) Chitwood, 1949, M. incognita (Kofoid & White, 1919) Chitwood 1949, and M. javanica (Treub, 1885) Chitwood, 1949 have been detected in vegetables and known to infest many crops in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, H. latipons was reported for the first time from two wheat growing areas, Kadınhanı and Yunak in Konya Province, by Rumpenhorst et al (1996). Later, it was reported from other areas and became recognized as a damaging pathogen for wheat-and barleyproducing areas in Central, Eastern, and Southeastern Anatolia and the Eastern Mediterranean regions of Turkey (Sahin et al, 2010;İmren et al, 2012Toktay et al, 2015). Heterodera latipons causes significant crop losses particularly in temperate climates in arid and semiarid regions, and its damage is exacerbated when combined with drought stress (Rivoal and Cook, 1993).…”
Section: Introductionmentioning
confidence: 99%